To the power of pi

Algebra Level 3

arccos ( x 2 + 1 2 x ) = x π \large \arccos \left(\frac x2 +\frac 1{2x} \right) =-x^\pi

If x x in the above expression is equal to a + b i a+bi , where a a and b b are real numbers, what is the value of a + b a+b (round to 2 decimal places)?

Notation: i i denotes the imaginary unit .


The answer is 1.38.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

1 solution

Louis Ullman
May 31, 2018

Recall Euler's Formula: e θ i = cos ( θ ) + i sin ( θ ) { e }^{ \theta i }=\cos { (\theta ) } +i\sin { (\theta ) } .

We can manipulate Euler's formula to look like the equation in the problem. But first, we'll have to get rid of the i sin ( θ ) i\sin { (\theta ) } by using the identity, sin ( θ ) = 1 cos ( θ ) 2 \sin { (\theta ) } =\mp \sqrt { 1-{ \cos { (\theta ) } }^{ 2 } } (which can be derived from the Pythagorean trigonometric identity).

The equation can now be rewritten as e θ i = cos ( θ ) i 1 cos ( θ ) 2 { e }^{ \theta i }=\cos { (\theta ) } \mp i\sqrt { 1-{ \cos { (\theta ) } }^{ 2 } } . After moving the real part to the left then squaring both sides, it can then be rewritten as ( e θ i ) 2 2 e θ i cos ( θ ) + cos ( θ ) 2 = 1 + cos ( θ ) 2 { ({ e }^{ \theta i }) }^{ 2 }-2{ e }^{ \theta i }\cos { (\theta ) } +{ \cos { (\theta ) } }^{ 2 }=-1+{ \cos { (\theta ) } }^{ 2 } , or ( e θ i ) 2 2 e θ i cos ( θ ) = 1 { ({ e }^{ \theta i }) }^{ 2 }-2{ e }^{ \theta i }\cos { (\theta ) } =-1 .

Now, we want to isolate the cosine. Moving ( e θ i ) 2 { ({ e }^{ \theta i }) }^{ 2 } to the right and dividing both sides by -1 results in the equation 2 e θ i cos ( θ ) = 1 + ( e θ i ) 2 2{ e }^{ \theta i }\cos { (\theta ) } =1+{ ({ e }^{ \theta i }) }^{ 2 } . Now all we need to do is divide both sides by 2 e θ i 2{ e }^{ \theta i } in order to get cos ( θ ) = 1 2 e θ i + e θ i 2 \cos { (\theta ) } =\frac { 1 }{ 2{ e }^{ \theta i } } +{ \frac { { e }^{ \theta i } }{ 2 } } . Finally, taking the arccosine of both sides results in arccos ( e θ i 2 + 1 2 e θ i ) = θ \arccos { (\frac { { e }^{ \theta i } }{ 2 } +\frac { 1 }{ 2{ e }^{ \theta i } } ) } =\theta .

It now becomes clear that x x is equivalent to e θ i { e }^{ \theta i } . Replacing x x with e θ i { e }^{ \theta i } , we get the equation arccos ( e θ i 2 + 1 2 e θ i ) = e θ π i \arccos { (\frac { { e }^{ \theta i } }{ 2 } +\frac { 1 }{ 2{ e }^{ \theta i } } ) } =-{ e }^{ \theta \pi i } . However, we already know that arccos ( e θ i 2 + 1 2 e θ i ) = θ \arccos { (\frac { { e }^{ \theta i } }{ 2 } +\frac { 1 }{ 2{ e }^{ \theta i } } ) } =\theta , meaning that θ \theta must be equal to e θ π i -{ e }^{ \theta \pi i } . The only value of θ \theta that would make that true is if θ \theta was equal to 1, as e π i = 1 { e }^{ \pi i }=-1 . This means that x x must be equal to e i { e }^{ i } , or approximately 0.540 + 0.841 i 0.540+0.841i .

The real part of 0.540 + 0.841 i 0.540+0.841i is 0.54, and the imaginary part is 0.841. Summing the two values together and rounding to two decimal points, we get our final answer, 1.38 \boxed { 1.38 } .

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...